A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Histoires d’objets - Fassa, Farinaz; Kraus, Cynthia; Malbois, Fabienne (Nouvelles Questions Feministes, 2005)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; féminisme radical; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis